Local Community Involvement and Quality of Life in Tourism Destination Development: Case of Coastal Tourism in West Java, Indonesia - Abdillah, Fitri (E-Journal of Tourism; Volume 3 Number 2 (September 2016), 2016)
The community in the tourism destination is one of the key elements to ensure the sustainability of the tourism destination itself. The objective of this study was to determine if the development of tourism contributes to the involvement and the level of quality of life of the local community in Pangandaran and Palabuhanratu. A total of 279 samples were obtained from two locations. Data were analyzed by using descriptive methods to determine the phase of the development of destinations, the community involvement, and the level of quality of life  The results showed that (1) Pangandaran has a better destination performance than Palabuhanratu, (2) Pangandaran is in the growth phase and Palabuhanratu is in the consolidation phase, (3) Increase in the number of tourist arrivals in destinations within the growth phase is more influential than that in the consolidation phase, and (4) Among the four components of quality of life, the material aspect has the highest value, followed by the spiritual, social and personal aspects. The development of tourism destinations significantly affected the level of community involvement and the level of quality of life.
Keywords: development; involvement; quality of life